Uncovering the hidden biodiversity of natural history collections: Insights from DNA barcoding and morphological characters of the Neotropical genus Orthocomotis Dognin (Lepidoptera: Tortricidae) - Razowski, Józef; Pelz, Volker; Tarcz, Sebastian (Zootaxa, 2017)
We used a 227-bp fragment of the mitochondrial gene cytochrome oxidase I (DNA “barcode”) in conjunction with morphological data to study specimens of the Neotropical genus Orthocomotis Dognin, 1906, acquired from natural history collections. We examined over 20 species of Orthocomotis from 17 localities in Colombia, Ecuador, and Peru. The analysis identified 32 haplotypes among the 62 specimens and found no haplotypes shared among species. The molecular study revealed not only the usefulness of short COI sequences in discriminating among Orthocomotis species but also showed distinctness of four clusters which correspond to those based on morphological (genitalia) characters. Moreover, the molecular results suggest the occurrence of rapid speciation in Orthocomotis. We hypothesize that this may be linked to the great biodiversity of potential host plants in Neotropical ecosystems.